"Synthesis, Mesomorphic and DFT Studies of Chalcone Derived Room Temperature Liquid Crystal with Presence of Lateral Nitro and N, N-Dimethyl Amino Terminal Group". (24th March 2019) - Shukla, Devendra K.; Sharma, Vinay S.; Prajapat, Varsha; Patel, R.B.
Abstract: In this present article, we wish to report on the liquid-crystalline properties of chalcone-ester based homologous series of compounds having aliphatic chain length in n-alkoxy group (n = 1 to 10, 12, 14, 16, 18). The present series consisted thirteen compounds, in which comp.C1 and C2 shows nonliquid crystalline properties, while comp.C3 to C7 display SmC phase and comp.C8 to C18 exhibits only nematic phase. Textural pattern of presently synthesized compounds are schlieren and threaded type. All this compounds were well characterized by elemental analysis, FT-IR and 1 H NMR. Phase transition temperatures of present synthesised compounds were determined by optical polarising microscopy (POM), differential scanning calorimetric (DSC). Detailed XRD investigation endorses the presence of the nematic phase in higher homologues and SmC phase in lower homologues. It is shown that chalcone with ester as linking unit favors a calamitic liquid crystalline behaviour in molecules. To get more insights, the DFT based HOMO, LUMO studies are carried out which supports intramolecular charge transfer interactions in this class of mesogens. Chalconyl ester based compounds C3 to C12 shows antibacterial as well as antifungal activity compared with corresponding standard drugs. Graphical Abstract: